Oil yield from Euphorbia tirucalli as an alternative bioenergy source in Tanzania - Nchimbi, Hamisi Yunus (Heliyon, 2021)
Due to the worldwide increase in the demands for bioenergy sources to replace fossil fuels. Euphorbia tirucalli oil produced by stems and modified leaves (phylloclades) is a valuable liquid fuel as an alternative energy source for biofuel production. In this study, E. tirucalli oils were extracted from stem barks with varying stem girths (20cm–80cm) and fully grown apical phylloclades. Soxhlet apparatus was used in oil extraction according to Luque de Castro and García (2000). The percentage (%) oil yield was calculated by the weight of extracted oil to the total weight of the dried sample (20g). The study hypothesized that significantly higher oil yields would be obtained from larger stem girths than phylloclades of the same trees in different Agro-Ecological Zones (AEZs). Likewise, the difference in oil yields was higher in the Semi-arid AEZ than in the Southern highland and the Coast AEZs (p > 0.05). Results showed slightly higher oil yields from large stem girths [16.47% ± 0.34%/(20g) max ≡ 82.35% ± 0.34%/(100g) max] than phylloclades [15.7% ± 0.49%/(20g) max ≡ 78.5% ± 0.34%/(100gmax] in different AEZs. Oil yields from Semi-arid [82.35% ± 0.34%/(100g) max and 78.5% ± 0.49%/(100g) max] were slightly higher than Southern highland [79.0% ± 0.34%/(100g) max and 76.4% ± 0.49%/(100g) max] and the Coast [76.4% ± 0.34%/(100g) max and 70.25% ± 0.49%/(100g) max] AEZ. But the difference in oil yields was not significant (p > 0.05). Results exhibited increasing patterns in the percentage (%) oil yields from low (20cm) to larger (80cm) stem girths. High oil yields between stem girths (82.35%) and phylloclades (78.5%) suggest that E. tirucalli oil is suitable for liquid biofuel production as an energy source in Tanzania.